Ecology of Endemic Primate Proboscis Monkeys at Curiak Island Area, South Kalimantan, Indonesia - Amalia Rezeki; Gusti Muhammad Hatta; Yudi Firmanul Arifin; Rizmi Yunita (Jurnal Multidisiplin Madani, 2023)
The proboscis monkey is an endemic primate of Borneo with an endangered conservation status. Proboscis monkey conservation must be carried out immediately, considering its existence as a biological indicator to maintain the balance of the wetland ecosystem. Proboscis monkey habitat which is outside the conservation area is very prone to changing functions, while the distribution of the proboscis monkey population is more outside the conservation area. The research aims to identify the ecology of proboscis monkeys that are outside the conservation area, namely the Curiak Island area in South Kalimantan. Retrieval of proboscis monkey ecological data for 6 months includes population, daily activities, and home range. The population method uses direct surveys by exploring the area using motor boats in the morning and evening. The daily activity method is the Scan Sampling Method and Ad liebetum Sampling. The home range method is recorded by tracking using a drone, the type of data recorded includes the total distance of daily movement which is calculated from the wake up time to sleep time. The results showed that the proboscis monkey population has the potential to develop with a distribution of 30 individuals divided into 3 groups, proboscis monkeys' daily activities include eating (33.5%), moving (11.63%), resting (41.56%), and social ( 13.28%). The average home range of proboscis monkeys is 86.25 m with a range of 49 m - 136 m